Interoperable Multi Conferencing Technology as a Basis for an Open, Global Web Conferencing Network - Roesler, Valter; Cecagno, Felipe; Marins, André; Stanton, Michael (My University, 2013)
Mconf is an open source, distributed, scalable and federated global web conferencing system, interoperable with SIP and mobile devices. The base for the system is an open source application called “Mconf: Multi conferencing with interoperable access for web and mobile devices”. This open source application explores a global approach to service provision. In June 2012 the Mconf Global Network [Roesler, 2012a] was launched, and by September 2013 had attained a global geographic distribution, with 23 servers distributed among three continents and about 1,500 communities and 5,500 users served worldwide through 10 web portals. This cooperating global network forms an open global web conferencing network that can support thousands of users daily. The problem addressed in this paper is: how this open multi conferencing technology can enable an open global academic web conferencing network. The answer is given by examples of R&D results of the experimental phase, and by explanations of: 1. How to keep all the servers up-to date and with the same software version, yet at the same time with custom themes and institution-based configurations. 2. How to generate real-time and historical usage statistics of the entire network and also for individual institutions. 3. How to guarantee availability in case of a server crash. 4. How to cope with surges in web conferencing traffic. 5. How to manage web conferencing recordings of such a large number of users and institutions scattered around the world.
Keywords: Global Web conferencing Network; Distributed systems; Scalability; Availability